RISK FACTORS AND CLINICAL PRESENTATION OF SEPTIC ARTHRITIS OF HIP IN INFANTS: A PROSPECTIVE STUDY - patil, Padmaraj; patil, Satish; Sonune, Pravin; Giradkar, Gourav (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to analyze the risk factors and clinical presentation of septic arthritis of hip in infants. Methods: Thirty infants with unilateral septic arthritis of hip were included in this study on the basis of a pre-defined inclusion and exclusion criteria. The study was conducted in PIOS Medilinks Pvt. Limited, Jaysingpur, Kolhapur, India. The duration of the study was 18 months from June 2021 to December 2022. The institutional ethical committee approved the study. The diagnosis of septic arthritis was made on the basis of Morrey’s criteria. Risk factors associated with septic arthritis and clinical presentation were studied. Results: Out of the total 30 infants diagnosed to be having septic arthritis of unilateral hip, 17 (57.67%) were males and 13 (43.33%) were females. In our study, an overwhelming majority of the patients belonged to neonatal age group (80%) followed by 1 month–2 months (10%). Only 3 infants were between 2 months and 1 year of age (10%). Low birth weight and prematurity or a combination of these two factors was the most common risk factor in neonates with septic hip arthritis and was seen in 7 (23.33%) patients. All infants having septic arthritis had increased local temperature (100%) and reduced joint movements (100%). Erythema (86.67%), swelling (73.33%), and irritability (60%) were other common clinical features associated with septic arthritis. The most common offending organism was Staphylococcus aureus (33.33%) followed by Klebsiella pneumoniae (13.33%). The analysis of outcome at the end of 3-month follow-up showed that out of 30 studied cases, 28 (93.33%) infants had a painless hip with normal range of motion. Conclusion: Septic arthritis of hip in infants is an emergency and requires prompt treatment. Any delay in diagnosis can have catastrophic consequences. However, in majority of appropriately managed infants, there is no residual damage to the affected joint.